Desvelando a relação entre ideologia, valores do indivíduo e estilo de consumo - Alexandre Maduro-Abreu; Antônio César Pinho Brasil Jr. (Ciências Sociais Unisinos)
This article aims to answer the question about the relationship between the values of an individual and their frequency of consumption. It develops a discussion on the theoretical and conceptual term “value”, on the formation of individualistic ideology and consumer society. For empirical verification, it applies three questionnaires validated in the literature to measure cultural values (ideologies), individual values and frequency of consumption in a population of 226 subjects. On the basis of the use of multivariate techniques of data analysis (correlations, regression and structural equations) and theoretical support, it was possible to coin the term “social elected”, meaning individuals who seek, on the basis of consumption, to demonstrate to society power, authority and status, independently of groups, legitimated by the values of freedom and equality, which guarantee that all can pursue the same condition of elected.